Consumer Preferences for Omnichannel Customer Service in Cosmetics Industry - Roman DOMANSKI; Lukasz HADAS; Hubert WOJCIECHOWSKI (Communications of International Proceedings, 2021)
Aim: The article analyses the way in which consumers purchase cosmetics. The research problem concerns the identification of channels chosen by consumers at various stages of the purchasing process. The aim of the article is to identify the scale of homogeneity (using only one channel) and heterogeneity (using two or more channels) along with the identification of the most and least numerous breaking points, i.e. the number of channel changes in the purchasing pathway. Methodology: In the theoretical part, a systematic literature review was carried out related to the terms omnichannel, maturity and cosmetics in the Web of Science database. The cosmetics market was also analysed on the basis of available industry reports. In the practical part, an original research approach was used, allowing the identification of consumers' individual decisions at each stage of the purchasing transaction - directly, at the source. The study was conducted in the form of a survey questionnaire. Findings: The topic of the sale of cosmetics in omnichannel conditions is undertaken by only 4 publications. The cosmetics industry is a dynamically developing and profitable market sector. The segment of hair and skin care cosmetics is currently on an upward trend. The obtained research results made it possible to identify the channels chosen by consumers at various stages of the purchasing process and to formulate guidelines for the management practice in the cosmetics industry in the area of multi-channel customer service development. Conclusions: Understanding the most and least preferred consumer behavioural patterns will make it possible to shape a service policy which properly addresses a given channel. Such knowledge is very important and valuable for cosmetics distributors, as it will allow to control consumers' choices by encouraging or discouraging them to use certain channels at different stages of the purchasing process.
Keywords: Omnichannel; Omnichannel Maturity; Purchasing Process; Cosmetics Industry; Sale Channel.